2010
DOI: 10.3758/app.72.1.236
|View full text |Cite
|
Sign up to set email alerts
|

Grab it! Biased attention in functional hand and tool space

Abstract: This study explored whether functional properties of the hand and tools influence the allocation of spatial attention. In four experiments that used a visual-orienting paradigm with predictable lateral cues, hands or tools were placed near potential target locations. Results showed that targets appearing in the hand's grasping space (i.e., near the palm) and the rake's raking space (i.e., near the prongs) produced faster responses than did targets appearing to the back of the hand, to the back of the rake, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
184
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(206 citation statements)
references
References 26 publications
(31 reference statements)
20
184
1
1
Order By: Relevance
“…This observation is consistent with the idea that attention is shifted ahead to a discrete action-relevant location. The finding replicates earlier studies showing that covert attention is allocated during hand movement planning (e.g., Baldauf et al, 2006;Fischer, 1997; for a review, see also Baldauf & Deubel, 2010) and with recent work exploring the effect of hand position on covert attention (Reed et al, 2010;Reed et al, 2006). Specifically, our findings show that attentional allocation is driven not only by hand placement in a resting state (i.e., holding the hand still in a certain location within the display), but also in continuous manual motion when this motion is visually concealed.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This observation is consistent with the idea that attention is shifted ahead to a discrete action-relevant location. The finding replicates earlier studies showing that covert attention is allocated during hand movement planning (e.g., Baldauf et al, 2006;Fischer, 1997; for a review, see also Baldauf & Deubel, 2010) and with recent work exploring the effect of hand position on covert attention (Reed et al, 2010;Reed et al, 2006). Specifically, our findings show that attentional allocation is driven not only by hand placement in a resting state (i.e., holding the hand still in a certain location within the display), but also in continuous manual motion when this motion is visually concealed.…”
Section: Discussionsupporting
confidence: 79%
“…Our main finding is a strong modulation of the previously established near-hand effect by the direction of hand movement. While previous work has either used static hands (e.g., Reed et al, 2010;Reed et al, 2006) or averaged across movement directions (Adam et al, 2012a), we showed an effect of hand movement direction when the hand was far from the probe location-namely, at the opposite side of the screen. In this condition, probe discrimination performance increased substantially when the hand moved toward the probe, as compared with when the hand moved away from the probe.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For example, Collins, Schicke, and Röder (2008) found increased attention on the effective part of the tool as well as on hand positions, with attention being generally higher at the tip of the tool. Reed et al (2010) showed that increased attention to the effective part of the tool after training with the same tool only occurs if the effective part of the tool is functionally relevant for the executed action. Whether or not attention is directed to the effective part of the tool or to the hand should be under strategic control.…”
Section: Discussionmentioning
confidence: 99%
“…One way to do this is to place visual stimuli in near-hand space. It was initially proposed that near-hand space incurs enhanced attentional processing (Reed, Betz, Garza, & Roberts, 2010;Reed, Grubb, & Steele, 2006) or reduced attentional disengagement (Abrams, Davoli, Du, Knapp, & Paull, 2008). More recently, however, there has been evidence to suggest that it is the purview of upregulated contribution of the magnocellular channel, which has greater temporal resolution but poorer spatial encoding, relative to its parvocellular counterpart (Gozli, West, & Pratt, 2012).…”
Section: Object Updating and Object Substitutionmentioning
confidence: 99%